2014
DOI: 10.1093/carcin/bgu042
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell-associated fatty acid synthase activates endothelial cells and promotes angiogenesis in colorectal cancer

Abstract: Upregulation of fatty acid synthase (FASN), a key enzyme of de novo lipogenesis, is associated with metastasis in colorectal cancer (CRC). However, the mechanisms of regulation are unknown. Since angiogenesis is crucial for metastasis, we investigated the role of FASN in the neovascularization of CRC. The effect of FASN on tumor vasculature was studied in orthotopic CRCs, the chick embryo chorioallantoic membrane (CAM) and Matrigel plug models using immunohistochemistry, immunofluorescent staining and confocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 35 publications
(59 reference statements)
1
68
0
3
Order By: Relevance
“…Fatty acid synthase (FASN) is a crucial enzyme in fatty acid biosynthesis, and catalyzes the formation of palmitate from acetyl-CoA and malonyl-CoA. Aberrant FASN function is associated with tumourigenesis in various human cancers, making it a potential cancer drug target [7375]. CAV1 and FASN are coordinately regulated in melanoma and prostate cancers, implying that their concomitant expression may enhance tumourigenesis [7678].…”
Section: Cav1 In Fatty Acid Metabolismmentioning
confidence: 99%
“…Fatty acid synthase (FASN) is a crucial enzyme in fatty acid biosynthesis, and catalyzes the formation of palmitate from acetyl-CoA and malonyl-CoA. Aberrant FASN function is associated with tumourigenesis in various human cancers, making it a potential cancer drug target [7375]. CAV1 and FASN are coordinately regulated in melanoma and prostate cancers, implying that their concomitant expression may enhance tumourigenesis [7678].…”
Section: Cav1 In Fatty Acid Metabolismmentioning
confidence: 99%
“…Reduction in FASN enzyme activity by chemical inhibitors including orlistat, cerulenin and triclosan have been reported to remarkably decrease progression in various cancer cell types [68]. FASN is an attractive therapeutic target as it regulates neoplastic transformation, metastasis as well as angiogenic pathways manipulating tumor vascularity and cell proliferation [69]. It also serves as a potential diagnostic and prognostic biomarker as it is secreted in the blood of patients with breast, prostate, colon and ovarian cancers compared with normal healthy subjects [69].…”
Section: Opg and Its Binding Partners In Breast Cancer Cellsmentioning
confidence: 99%
“…FASN is an attractive therapeutic target as it regulates neoplastic transformation, metastasis as well as angiogenic pathways manipulating tumor vascularity and cell proliferation [69]. It also serves as a potential diagnostic and prognostic biomarker as it is secreted in the blood of patients with breast, prostate, colon and ovarian cancers compared with normal healthy subjects [69]. In our recent study we demonstrated that compared to HMEC, SUM149PT and SUM1315MO2 breast cancer cells express increased level of FASN [70].…”
Section: Opg and Its Binding Partners In Breast Cancer Cellsmentioning
confidence: 99%
“…It has been suggested that inhibition of FASN may prevent or inhibit metastasis in colorectal cancer (41) and the FASN inhibitor orlistat was shown to decrease angiogenesis and metastases in experimental models (42,43). We tested the ability of C75 to inhibit migration of prostate cancer cells.…”
Section: Figmentioning
confidence: 99%